Understanding Mortgage Spreads - Nina Boyarchenko; Andreas Fuster; David O. Lucca (Federal Reserve Bank of New York, 2014)
Spreads of agency mortgage-backed securities (MBS) vary significantly in the cross section and over time, but the sources of this variation are not well understood. We document that, in the cross section, MBS spreads adjusted for the prepayment option show a pronounced smile with respect to the MBS coupon. We propose prepayment model risk as a candidate driver of MBS spreads and present a new pricing model that uses "stripped" MBS prices to identify the contribution of this risk to option-adjusted spreads. With this pricing model, we find that prepayment model risk explains the smile, while the variation in the time series is mostly accounted for by a non-prepayment-risk component, which is related to credit risk in fixed-income markets and MBS supply. Finally, we study the MBS market response to the Fed's large-scale asset purchases and show that the model is consistent with spread movements following the initial announc ement and, in particular, the fanning out of option-adjusted spreads across different coupons.
Keywords: G10; G12; G13; 330; agency mortgage-backed securities; option-adjusted spreads; prepayment model risk; OAS smile